2020
DOI: 10.1007/s00423-020-02038-z
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical treatment of colonic Crohn’s disease: a national snapshot study

Abstract: Aim The different surgical options for patients with colonic Crohn’s disease (CD) include segmental colectomy, subtotal colectomy or proctocolectomy with end ileostomy. We present a national, multicentre study, promoted by the Italian Society of Colorectal Surgery with the aim to collect benchmark data and national variations on multidisciplinary management and postoperative outcomes of patients undergoing surgery for colonic CD. Methods All adult patients having elective surgery for colonic CD from June 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Surgical strategies for CD include IR with primary anastomosis or temporary stoma creation followed by delayed anastomosis. The latter is intended to reduce the occurrence of serious complications such as IASC and anastomotic fistula, especially for penetrating disease[ 45 - 47 ] and colonic CD[ 48 , 49 ]. In the cases included in this study, 59.1% of patients underwent staged surgery, and neither penetrating disease nor colectomy was found to be an independent risk factor for major postoperative complications, which again indicates that reasonable selection of staged surgery can effectively reduce postoperative IASC.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical strategies for CD include IR with primary anastomosis or temporary stoma creation followed by delayed anastomosis. The latter is intended to reduce the occurrence of serious complications such as IASC and anastomotic fistula, especially for penetrating disease[ 45 - 47 ] and colonic CD[ 48 , 49 ]. In the cases included in this study, 59.1% of patients underwent staged surgery, and neither penetrating disease nor colectomy was found to be an independent risk factor for major postoperative complications, which again indicates that reasonable selection of staged surgery can effectively reduce postoperative IASC.…”
Section: Discussionmentioning
confidence: 99%
“…The reported recurrence rate after this procedure is low, and TPC appears to be the best surgical option to reduce the risk of recurrence [39]. In addition, a recent metaanalysis concluded that segmental colectomy, subtotal colectomy, and proctocolectomy may be equally effective in patients with colonic CD [41].…”
Section: Proctocolectomymentioning
confidence: 99%
“…Despite the immediate relief of symptoms and a potential increase of quality of life after CD surgery[ 5 ], important concerns are the risk of potential (severe) complications and recurrence of CD[ 6 ]. Reports on the frequency of postoperative complications, following intestinal resection in CD patients, range from 20%-47%[ 7 - 12 ]. Several general and CD-specific risk factors for postoperative complications have been identified.…”
Section: Introductionmentioning
confidence: 99%